HUMANISME SEKULER VERSUS HUMANISME RELIGIUS (Kajian Tentang Landasan Filosofis dan Upaya Menemukan Alternatif Melalui Pemikiran Seyyed Hossein Nasr) - Masduki Masduki (Lembaga penelitian dan pengabdian kepada masyrakat, 2011)
Spritual’s humanism gets opportunity be made as base of induvidu’s development alternative and society. Humanism relogiousing to emphaseize spritual’s point actualization in induvidu’s life and society. As induvidu, intrinsic spiritual point gets to make insan kamil. Meanwhile as society become ideal society